How does trade freedom affect the development of clean energy? based on the moderating effect of carbon emissions - Wu, Yan (Frontiers in Environmental Science, 2025)
Changes in trade freedom affect national economic development and energy demand, which in turn affects clean energy development. This study assesses the impact of trade freedom on clean energy development in 114 countries from 2006 to 2020. Empirical testing shows that trade freedom significantly inhibits clean energy development in a linear manner. The results also indicate that higher GDP per capita and increased governmental capacity to control corruption are both important factors contributing to clean energy development. In addition, by incorporating mediating mechanisms, this study finds that trade freedom inhibits clean energy development by increasing a country’s innovation and trade openness. Finally, by exploring possible moderating effects, the results show that carbon emissions and bank lending weaken the negative effect of trade freedom on clean energy development, while globalization and government expenditure strengthen this effect. This study offers vital insights to policymakers in balancing the advancement of national trade liberalization policies with clean energy development.